2020
DOI: 10.21873/invivo.12168
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Zinc Chloride on the Suppression of Hepatitis A Virus Replication by Interferon in Human Hepatoma Huh7 Cells

Abstract: Background/Aim: Hepatitis A virus (HAV) infection is still one of the serious health problems worldwide, despite the existence of effective vaccines for HAV. Zinc compounds have antiviral activities against various DNA and RNA viruses. Therefore, we investigated the effects of zinc compounds on the antiviral activity of interferon against HAV. Materials and Methods: The effects of zinc compounds with or without interferon on HAV genotype IIIA HA11-1299 replication were examined in human hepatoma Huh7 cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In the present study, we revealed the following: (i) zinc chloride affects the TLR signaling pathways in human hepatocytes; (ii) MAP2K3 expression is downregulated by zinc chloride; and (iii) HAV replication is downregulated by the silencing MAP2K3 expression. Our results explained one of the different mechanisms of the inhibitory effects of zinc compounds on HAV replication from previous reports [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the present study, we revealed the following: (i) zinc chloride affects the TLR signaling pathways in human hepatocytes; (ii) MAP2K3 expression is downregulated by zinc chloride; and (iii) HAV replication is downregulated by the silencing MAP2K3 expression. Our results explained one of the different mechanisms of the inhibitory effects of zinc compounds on HAV replication from previous reports [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 83%
“…We previously reported that a treatment of 5 μM zinc chloride for 72 h suppressed HAV genotype IIIA HA11-1299 replication by 62.2% compared with the untreated control in human hepatoma Huh7 cells [ 10 ]. We also observed the additive effects of zinc chloride on the suppression of HAV replication by interferon-α-2a in Huh7 cells [ 10 ]. It is well known that TLR signaling pathways are involved in the eradication of RNA viruses [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HAV vaccination could prevent MSM from experiencing acute HAV infection, and HAV vaccination should be useful in preventing other people from being infected with HAV. It is possible that the administration of antivirals against HAV would be useful for the prevention of severe HAV infection [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%